2021
DOI: 10.1590/1678-5150-pvb-6697
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition to acute pancreatitis in dogs with severe acute renal failure

Abstract: Patients with acute renal failure often have a negative energy balance, which promotes metabolic changes predisposing to complications. The objective of this study was to evaluate laboratory parameters of 30 dogs with severe acute renal failure, to assess their relationship with the possibility of developing acute pancreatitis due to the negative energy balance, and to correlate these findings with the degree of renal failure. Serum concentrations of urea, creatinine, beta-hydroxybutyrate, triglycerides, amyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Moreover, cPL concentrations were measured at the request of clinicians in the latter study, presumably because AP was suspected, but DGGR‐lipase was measured in our study regardless of clinicians' suspected diagnoses. Similarly, another study found cPL concentrations ≥400 μg/L either at admission or within the first 8 days of hospitalization in 71% of 28 dogs with AKI of IRIS Grades 3–5 not undergoing HD 14 . Lipase activity also was measured in that study and reported to be significantly higher in dogs with AKI compared to healthy control dogs, but neither the assay method nor the prevalence of increased lipase activity were disclosed.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Moreover, cPL concentrations were measured at the request of clinicians in the latter study, presumably because AP was suspected, but DGGR‐lipase was measured in our study regardless of clinicians' suspected diagnoses. Similarly, another study found cPL concentrations ≥400 μg/L either at admission or within the first 8 days of hospitalization in 71% of 28 dogs with AKI of IRIS Grades 3–5 not undergoing HD 14 . Lipase activity also was measured in that study and reported to be significantly higher in dogs with AKI compared to healthy control dogs, but neither the assay method nor the prevalence of increased lipase activity were disclosed.…”
Section: Discussionmentioning
confidence: 83%
“…We found that high DGGR‐lipase activity at admission and particularly during hospitalization was associated with high IRIS grades, although correlation of DGGR‐lipase activity and plasma creatinine concentrations at admission was poor. One previous study in dogs, in which cPL concentrations ≥400 μg/L were measured within 1–8 days of admission in 71% of 28 dogs with IRIS Grades 3–5, found a positive correlation between cPL and plasma creatinine concentrations, which was interpreted as evidence of predisposition to AP in dogs with severe AKI 14 . However, dogs with AKI were compared to healthy controls and the extent to which the severity of AKI was associated with increased cPL concentrations was not evaluated.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations